Compare the Mean Non Hypoxic Apnea Duration of 20° Head up with Conventional Supine Position during Pre-oxygenation in Patients Undergoing Elective Surgery - Tanzeela Firdous, Ali Kashif, Sahira Nawaz Khan, Ayesha Waqar, Sufyan Ali, Sumayya Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Pre-oxygenation is routinely carried out before general anaesthesia with the aim of maximizing oxygen stores in the functional residual capacity of the lungs. This’s a method to avoid hypoxia during the apnoeic interval after general anesthetic induction. When initiating general anaesthesia, it is a practice to pre-oxygenate for 3 minutes in the supine position, since this is considered to be related with reduced cardiovascular instability. While the best timing for pre-oxygenation has been found, the best body posture for pre-oxygenation has yet to be determined. Objective: To compare the mean non hypoxic apnea duration of 20° head up with conventional supine position during pre-oxygenation in patients undergoing elective surgery Design of the study: Randomized Controlled Trial Setting: This study was conducted in the Operative Rooms of Jinnah Hospital, Lahore Result: Total 200 patients included, the mean age was 26.21+5.21 in Group A & 24.87+4.69 in Group B. The age range was 15-50 years, 41%(n=41) in Group A 39%(n=39) & in Group B between 15-25 years of age which was in majority. There were 45(45%) males and 55(55%) in Group A & 51.0(51%) male and 49.0(49%) female in Group B which shows that basic demographics were insignificant in both groups while comparing the mean non hypoxic apnea duration of 20° head up with conventional supine position during pre-oxygenation in patients undergoing elective surgery, we revealed 352.28+74.43 in Group A and 449.75+67.31 in Group B, p value was calculated as 0.04 i.e. ≤0.05 Conclusion: Comparison of the average non hypoxic apnea duration of 20° head up with conventional supine position during pre-oxygenation in patients undergoing elective surgery reveals prolonged duration in patients with 20° head up than conventional supine position during pre-oxygenation. Keywords: Mean non hypoxic apnea duration, 20° head up, conventional supine position, pre-oxygenation